Predicting emotional health indicators from linguistic evidence of psychological distancing. (30th January 2019) - Shahane, Anoushka D.; Denny, Bryan T.
Abstract: Psychological distancing, a form of cognitive reappraisal, involves construal of emotionally valenced stimuli in an objective manner, or with perceived spatial and temporal distance. Prior work suggests that in appropriate contexts, reappraisal broadly, and distancing specifically, is related to adaptive mental and physical health outcomes. Additionally, recent research suggests that shifting language to be more distant (i.e., linguistic distancing [LD]) can have adaptive emotion regulatory effects. The present study addressed whether LD is also associated with adaptive health indicators. Participants transcribed their thoughts while viewing negative or neutral stimuli in one of three ways: (a) by implementing objective language, (b) by implementing spatially and/or temporally far away language, or (c) by responding naturally. Across psychological distancing groups, LD was associated with lower negative affectivity (lower perceived stress and depression symptoms), better general well‐being (better emotional well‐being and energy and vitality), and better emotion regulation (ER; greater reappraisal frequency and fewer difficulties in implementing ER). Participants who used more LD in the objective group had lower negative affectivity, better general well‐being, and better ER, and those in the far group had better ER. The results reveal linguistic mechanisms underlying ER and its relationship to health indicators, suggesting future examination of LD interventions.